2021
DOI: 10.1186/s40959-021-00125-8
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing cardiovascular disease increases risk of atrial arrhythmia and mortality in cancer patients treated with Ibrutinib

Abstract: Background Ibrutinib is a Bruton’s tyrosine kinase inhibitor used in the treatment of hematological malignancies. The most common cardiotoxicity associated with ibrutinib is atrial arrhythmia (atrial fibrillation and flutter). It is known that patients with cardiovascular disease (CVD) are at an increased risk for developing atrial arrhythmia. However, the rate of atrial arrhythmia in patients with pre-existing CVD treated with ibrutinib is unknown. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In a meta-analysis of four randomized clinical trials of patients with CLL, SLL, and mantle cell lymphoma treated with ibrutinib vs non-ibrutinib therapy, the pooled incidence rate of AF in the ibrutinib group was 3.3 per 100 years compared to 0.84 per 100 person years in the nonibrutinib group [21]. Avalon JC et al also found that pre-existing cardiovascular disease was associated with a signi cantly higher rates of atrial brillation/arrhythmias as well as mortality in those receiving treatment with ibrutinib [22].…”
Section: Discussionmentioning
confidence: 98%
“…In a meta-analysis of four randomized clinical trials of patients with CLL, SLL, and mantle cell lymphoma treated with ibrutinib vs non-ibrutinib therapy, the pooled incidence rate of AF in the ibrutinib group was 3.3 per 100 years compared to 0.84 per 100 person years in the nonibrutinib group [21]. Avalon JC et al also found that pre-existing cardiovascular disease was associated with a signi cantly higher rates of atrial brillation/arrhythmias as well as mortality in those receiving treatment with ibrutinib [22].…”
Section: Discussionmentioning
confidence: 98%
“…A single-center retrospective review of new onset AF in 217 ibrutinib-treated patients identified a 3-fold increased risk of AF and increased adjusted all-cause mortality in patients with prior coronary artery disease, congestive heart failure, pulmonary hypertension, moderate valvular heart disease, and cardiac device implantation. 25 It would be prudent to evaluate all CLL patients for prior cardiac disease before initiating ibrutinib.…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 retrospective chart review from a single institution investigated whether patients with pre‐existing CVD had a higher likelihood of developing new AF than those with no prior CVD, following treatment with ibrutinib [ 31 ]. It was found that patients with prior CVD were 2.91 times more likely to develop AF than those without prior CVD, although this study was limited by its small sample size, and the sample of patients came from a single institution.…”
Section: Discussionmentioning
confidence: 99%